2016
DOI: 10.1002/jsfa.7681
|View full text |Cite
|
Sign up to set email alerts
|

Health‐promoting bioactivities of betalains from red dragon fruit (Hylocereus polyrhizus (Weber) Britton and Rose) peels as affected by carbohydrate encapsulation

Abstract: The study showed that the antioxidant, anti-inflammatory, antiangiogenic and GST-inducing activities of betalains from red dragon fruit peels were enhanced through carbohydrate encapsulation. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 50 publications
(57 reference statements)
1
21
0
2
Order By: Relevance
“…However, to corroborate the first hypothesis, a positive correlation between betaxanthins and antiangiogenic activity (r > 0.5176) as well as with the haemoglobin content (r > 0.4475) was also found. Some studies have shown previously the dose-dependent anti-angiogenic properties of betalains (Ninfali, Antonini, Frati, & Scarpa, 2017;Rodriguez et al, 2016). The angiogenesis inhibition seems due to their ability to scavenge the reactive oxygen species and to induce apoptosis on CD31+ microvessel endothelial cells (Zhang, Pan, Wang, Lubet, & You, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, to corroborate the first hypothesis, a positive correlation between betaxanthins and antiangiogenic activity (r > 0.5176) as well as with the haemoglobin content (r > 0.4475) was also found. Some studies have shown previously the dose-dependent anti-angiogenic properties of betalains (Ninfali, Antonini, Frati, & Scarpa, 2017;Rodriguez et al, 2016). The angiogenesis inhibition seems due to their ability to scavenge the reactive oxygen species and to induce apoptosis on CD31+ microvessel endothelial cells (Zhang, Pan, Wang, Lubet, & You, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…The angiogenesis inhibition seems due to their ability to scavenge the reactive oxygen species and to induce apoptosis on CD31+ microvessel endothelial cells (Zhang, Pan, Wang, Lubet, & You, 2013). In fact, reactive oxygen and nitrogen species are inflammatory and angiogenesis modulators able to influence vessel formation (Rodriguez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Basic medical research has revealed that betalain‐rich extracts possess anti‐inflammatory and anticancer properties (Kapadia et al ., ; Lechner et al ., ; Martinez et al ., ; Rodriguez et al ., ). Although more than 50 molecular species of betalains have been reported (Delgado‐Vargas et al ., ), very few exhibit biological activity.…”
Section: Introductionmentioning
confidence: 97%
“…The horizontal axis indicates the retention time (min), whereas the vertical axis indicates the signal intensity (lV). Rodriguez et al, 2016). Although more than 50 molecular species of betalains have been reported (Delgado-Vargas et al, 2000), very few exhibit biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used natural food pigments include anthocyanins, carotenoids, betalains, and chlorophylls, among others. In addition to their food application, the consumption of these natural‐colored compounds has been associated with a reduction of noncommunicable diseases such as cancer, diabetes, and obesity (Li and others ; Cooperstone and Schwartz ; Rodriguez and others ). This effect implies a value‐added concept for natural pigments utilization.…”
Section: Introductionmentioning
confidence: 99%